IP-10 release assays in the diagnosis of tuberculosis infection: current status and future directions. (March 2012) - Ruhwald, Morten; Aabye, Martine G; Ravn, Pernille
The current state-of-the-art tests for infection with Mycobacterium tuberculosis – the IFN-γγ release assays – rely on accurate measurement of the cytokine IFN-γγ. Many other potential biomarkers are expressed in concert with IFN-γγ, and IP-10 in particular has shown promising results. IP-10 is produced in large amounts, allowing for the development of new and simplified test platforms, such as lateral flow. In this review, we summarize the results of 22 clinical studies exploring the use of IP-10 as an alternative marker to IFN-γγ. The studies report that diagnostic accuracy of IP-10 is on par with IFN-γγ, but also that IP-10 may be more robust in young children and in HIV-infected individuals with low CD4 cell counts. We conclude the review by presenting limitations of the published works and outline recent developments and future directions.